Body weight and United States economic development, 1840-1940. - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2019)
When traditional measures for material and economic welfare are scarce or unreliable, height and the body mass index (BMI) are now widely accepted measures that represent cumulative and current net nutrition in development studies. However, as the ratio of weight to height, BMI does not fully isolate the effects of current net nutrition. After controlling for height as a measure for current net nutrition, this study uses the weight of a sample of international men in US prisons. Throughout the late 19th and early 20th centuries, individuals with darker complexions had greater weights than individuals with fairer complexions. Mexican and Asian populations in the US had lower weights and reached shorter statures. Black and white weights stagnated throughout the late 19th and early 20th centuries. Agricultural workers' had greater weights than workers in other occupations.
Keywords: I10; J11; J71; N31; 330; weight; 19th century current net nutrition; US race relations